Estudos micromorfológicos em Portulaca L. (Portulacaceae) do Brasil - Santos, Thaíla Vieira Alves dos (2016)
Portulaca hirsutissima is a succulent herb that occurs in open fields, sandy or rocky soil in distinct regions in Brazil, belonging to the Portulacaceae family. We analyzed the external morphology, seeds and pollen grains in representatives of this species and related morphotypes along their known distribution. We observed a consistent variation in their micromorphology and two new species are here described and illustrated. Portulaca giuliettiae occurs in Eastern Brazil, from Paraiba to Rio de Janeiro and P. goiasensis is restricted to the Chapada dos Veadeiros, in Central Brazil, while P. hirsutissima is now considered as restricted to Minas Gerais State.